Optimal Disturbance Rejection Control of Underactuated Autonomous Underwater in Vertical Plane - Yang Qing; Gao De-xin (Institute of Advanced Engineering and Science, 2015)
To realize the optimal control of underactuated autonomous underwater vehicle (AUV) in vehicle plane with external disturbances, a optimal disturbance rejection controller is proposed with respect to the quadratic performance indexes. Firstly, the depth control model of underactuated AUV system and the wave model is proposed; Then based on the theory of the quadratic optimal control and stability degree constraint, a feedforward and feedback optimal disturbance rejection control law with a higher mean-square convergence rate is derived from the Riccati equation and the Sylvester equation, which can reject the disturbance influence to AUV. Finally, the controller is applied to the dive plane control of AUV with wave force disturbances, and the results demonstrate the effectiveness and robustness of the controller. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6889